2019
DOI: 10.2147/amep.s154974
|View full text |Cite
|
Sign up to set email alerts
|

<p>Medical student mentoring programs: current insights</p>

Abstract: Medical school mentoring programs incorporate a wide range of objectives. Clinical mentoring programs help to develop students’ clinical skills and can increase interest in under-subscribed specialties. Those that focus on teaching professionalism are integrated into medical school curriculums in order to overcome the “hidden curriculum”. Positive mentoring plays a part in reversing the decline of academic medicine, by sparking interest through early research experiences. It also has an important role in encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
125
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 81 publications
(225 reference statements)
3
125
0
16
Order By: Relevance
“…Social support, as expressed by mentees, is a contributor to building camaraderie and problem‐solving skills not only for students but for URM faculty members as well (Kosoko‐Lasaki et al, 2006). Mentoring, by peers or faculty, has also demonstrated in medical school to foster other soft skills needed for success such as confidence, professionalism, and critical inquiry (Nimmons et al, 2019). Given the previously mentioned findings in medical students, it can be hypothesized that similar non‐cognitive attributes related to the peer‐mentorship of this investigation must have contributed to the success of URM students.…”
Section: Discussionmentioning
confidence: 99%
“…Social support, as expressed by mentees, is a contributor to building camaraderie and problem‐solving skills not only for students but for URM faculty members as well (Kosoko‐Lasaki et al, 2006). Mentoring, by peers or faculty, has also demonstrated in medical school to foster other soft skills needed for success such as confidence, professionalism, and critical inquiry (Nimmons et al, 2019). Given the previously mentioned findings in medical students, it can be hypothesized that similar non‐cognitive attributes related to the peer‐mentorship of this investigation must have contributed to the success of URM students.…”
Section: Discussionmentioning
confidence: 99%
“…From the bene ts described, it is evident that the bi-weekly meetings with resident mentors were an opportunity for the medical students to discuss their mentorship experiences among peers, as well as receive advice and support from resident mentors, especially when faced with di cult situations. These meetings were also an opportunity for career mentorship, as many programs providing mentorship to medical students tend to initiate [17].…”
Section: Discussionmentioning
confidence: 99%
“…Medical students are also often mentees in mentoring relationships with senior medical trainees and physicians. A review of such mentorship programs identi ed bene ts for medical student mentees in clinical knowledge and skills attainment, professional development, communication skills development, exposure to subspecialties, career guidance, and opportunities for networking and research involvement [17]. However, development of health advocacy competencies in medical students through physician mentorship remains a poorly described area of study.…”
Section: Introductionmentioning
confidence: 99%
“…Various mentorship domains, such as socio-emotional (e.g., psycho-social support) and instrumental (e.g., research task support, learning task support) mentoring, have been positively associated with students' identity as learners, their sense of belonging, and their confidence to function as future professionals [13,14]. These factors have also been associated with increased interest and commitment to learning and engaging in research [15][16][17]. Undergraduate student learning and research experiences have also been shown to effectively increase their interest, motivation, and preparedness for professional practice with a positive mentoring relationship often cited as a key element in these outcomes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%